On the Efficient Influence Function and the Efficient Score Function - Andries Lenstra (Tinbergen Institute, 1997)
Efficient influence functions and efficient score functions are representations of derivatives of maps. The invariance of theformer under changes of parametrization, and the formula relating the efficient influence function for the projection of aparameter to the efficient score function, turn out to be immediate results of diagram chasing, rather than following fromformal calculations.
Keywords: 330; Mathematik; Theorie